Vancomycin Prophylaxis for Total Joint Arthroplasty: Incorrectly Dosed and Has a Higher Rate of Periprosthetic Infection Than Cefazolin. Issue 7 (July 2017) - Kheir, Michael M.; Tan, Timothy L.; Azboy, Ibrahim; Tan, Dean D.; Parvizi, Javad
Abstract: Background: In total joint arthroplasty (TJA), vancomycin is used as perioperative antibiotic prophylaxis in patients with penicillin allergy or in patients colonized with methicillin‐resistant Staphylococcus aureus (MRSA). Although vancomycin dosing should be weight‐based (15 mg/kg), not all surgeons are aware of this; a fixed 1‐g dose is instead frequently administered. Questions/purposes: (1) Is there a difference in the risk of periprosthetic joint infection (PJI) in patients receiving vancomycin or cefazolin prophylaxis after primary TJA? (2) What proportion of patients is adequately dosed with vancomycin? (3) Compared with actual fixed dosing, does weight‐based dosing result in a greater proportion of patients staying above the recommended 15‐mg/L level at the beginning and end of surgery? (4) Are patients overdosed with vancomycin at greater risk of developing nephrotoxicity and acute kidney injury? Methods: A single‐institution, retrospective study was performed on 1828 patients undergoing primary TJAs who received vancomycin prophylaxis between 2008 and 2014. During the same period, 5810 patients underwent primary TJA and received cefazolin monotherapy. A chart review was performed to obtain patient characteristics, antibiotic dose and timing of administration, and microbiology data. Adequate vancomycin dosing was defined as 15 mg/kg and within the 125‐mg range. Vancomycin levels were calculated at the beginning and end of surgery using pharmacokinetic equations. Levels of 15 mg/L were considered adequate. Logistic regression, chi square tests, and analysis of variance were performed. Results: Among primary TJAs, patients receiving vancomycin had a higher rate of PJI (32 of 1828 [2%]) compared with patients receiving cefazolin prophylaxis (62 of 5810 [1%]; adjusted odds ratio, 1.587 [1.004‐2.508]; p = 0.048). Ten percent of PJIs in the vancomycin underdosed group (two of 20) was caused by MRSA, and no patients with adequate dosing or overdosing of vancomycin developed PJI with MRSA. Of all procedures in which vancomycin monotherapy was used, 28% (518 of 1828) was adequately dosed according to weight‐based dosage recommendations. Furthermore, 94% (1726 of 1828) of patients received a fixed 1‐g dose of vancomycin, of whom 64% (1105 of 1726) were underdosed. All patients had vancomycin infusion initiated within 2 hours before incision. A weight‐based protocol would have resulted in fewer patients having unacceptably low vancomycin levels (< 15 mg/L) compared with those with actual fixed dosing, both for the beginning of surgery at the time of incision (zero of 1828 [0%] versus 471 of 1828 [26%]; odds ratio, 0.001 [0.000‐0.013]; p < 0.001) and at the end of surgery (33 of 1828 [2%] versus 746 of 1828 [41%]; odds ratio, 0.027 [0.019‐0.038]; p < 0.001). Between the vancomycin dosage groups, there were no differences in the rate of nephrotoxicity (underdosed: 12 of 1130 [1%], adequately dosed: five of 518 [1%], overdosed: four of 180 [2%], p = 0.363) and acute kidney injury (underdosed: 28 of 1130 [2%], adequately dosed: 10 of 518 [2%], overdosed: six of 180 [3%], p = 0.561). Conclusions: The majority of patients given vancomycin prophylaxis are underdosed according to the weight‐based dosage recommendations, and MRSA did not occur in patients who were adequately dosed with vancomycin. Surgeons should thus ensure that their patients are adequately dosed with vancomycin using the recommendation of 15 mg/kg and that the dose of vancomycin is administered in a timely fashion. Furthermore, and based on the findings of this study, we have moved toward limiting the utilization of vancomycin prophylaxis for patients undergoing elective arthroplasty at our institution. Level of Evidence: Level III, therapeutic study.